Exploring The Cultural Diversity Of Indonesia Through Traditional Mask Art - Syafrida Syafrida; Agustina, Sri; Usmaidar Usmaidar (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This study explores the use of traditional mask art as an educational medium to introduce Indonesian cultural diversity and strengthen cultural identity among children of Indonesian migrant workers in Malaysia. Employing a qualitative descriptive approach, the research was conducted at Sanggar Sri Muda involving 28 participants selected purposively based on their engagement in an international community service (KKN Internasional) program. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing.The findings reveal that the implementation of interactive and participatory art-based learning significantly enhances students’ engagement, cultural awareness, and understanding of symbolic meanings embedded in traditional mask art. Participants demonstrated improved recognition of cultural values such as moral character, identity representation, and local wisdom. Furthermore, the activity fostered a stronger sense of cultural pride and belonging among students who initially had limited exposure to Indonesian heritage.Despite these positive outcomes, several challenges were identified, including limited instructional time, varying levels of prior cultural knowledge, and resource constraints. These limitations indicate the need for more structured and sustainable cultural education programs.Overall, this study highlights the potential of traditional mask art as an innovative and effective pedagogical tool in promoting cultural literacy and reinforcing national identity among diaspora children. The findings contribute to the development of culturally responsive education strategies and support broader efforts in preserving intangible cultural heritage in a globalized context.